Multiple Keratoacanthomas, Philadelphia Chromosome+ Acute Lymphoblastic Leukemia, and Dasatinib: A Case Report - Siddhant Thukral; Lloyd E. King Jr; Lloyd E. King Jr; David H. Horowitz (University Library System, University of Pittsburgh, 2015)
Background: Treatment for adult Philadelphia chromosome+ acute lymphoblastic leukemia includes using dasatinib, a tyrosine kinase inhibitor. Cutaneous squamous cell carcinomas and keratoacanthomas are common findings in patients treated with BRAF inhibitors of tyrosine kinases. No documentation of dasatinib inducing multiple keratoacanthomas, squamous cell carcinomas type during treatment of Philadelphia chromosome+ acute lymphoblastic leukemia is currently available. Case: A 77-year-old Caucasian male presented to the dermatology clinic two months after starting treatment with dasatinib for Philadelphia chromosome positive+ acute lymphoblastic leukemia. Biopsies confirmed the lesions on the arms, chest, legs and back as keratoacanthoma (KA) type of squamous cell carcinomas (SCCs). The cutaneous lesions were surgically removed and no new or recurrent lesions were detected since their initial rapid onset despite continued dasatinib therapy. Conclusion: This report of the rapid onset of keratoacanthoma type squamous cell carcinomas in a patient with Philadelphia chromosome+ acute lymphoblastic leukemia treated with dasatinib is presumed to be the first due to the rarity of adult Philadelphia chromosome+ acute lymphoblastic leukemia. This report documents another tyrosine kinase inhibitor that is associated with the eruption of keratoacanthomas, and adds to the literature regarding the regularity of this relatively common side effect, which may have treatment other than surgery if only a few lesions are present.